The Effect of Long-Acting Beta-2 Agonist Monotherapy and Long-Acting Anticholinergic Monotherapy to Quality-of-Life in Group B Stable COPD Patients - Tri Setia Negara Sinulingga; Pandiaman Pandia; Amira P. Tarigan; Putri Chairani Eyanoer (Jurnal Respirologi Indonesia, 2022)
Background: Based on the 2019 Global Initiative for Chronic Obstructive Lung Disease (GOLD), treatment for group B stable COPD patients is a long-acting beta-2 agonist (LABA) or long-acting anticholinergic (LAMA). Some studies experienced that LAMA was better than LABA but the opposite was also found in several studies. COPD patients often experience a decline in physical activity which causes a decrease in quality of life. We aimed to compare the effect of LABA or LAMA on quality of life in group B stable COPD patients.Methods: This was a study with case series design conducted on 50 COPD patients divided into two groups. The first group consisted of patients who used LABA for at least 3 months. The second group used LAMA for at least 3 months. All subjects filled in the SGRQ. The calculation of SGRQ was carried out using Microsoft Excel Calculator SGRQ.Results: A total 41 men and 9 women were enrolled in this study. There was no significant difference between the use of indacaterol monotherapy and tiotropium monotherapy on the quality of life although tiotropium showed a better quality of life (76%) than indacaterol monotherapy (64%).Conclusion: There was no significant difference in the use of indacaterol and tiotropium on the quality of life although in this case tiotropium showed better results (P=0.538).